2008
DOI: 10.1590/s1677-55382008000500003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lovastatin on conventional medical treatment of lower urinary tract symptoms with finasteride

Abstract: Objective: To explore whether or not statins have any impact on the progression of components of benign prostatic hyperplasia (lower urinary tract symptoms severity, prostate volume and serum prostate specific antigen (PSA) when combined with other agents inhibiting growth of prostate cells. Materials and Methods:This was a preliminary, clinical study. Eligible patients were aged > 50 yrs, with International Prostate Symptom Score (IPSS) between 9 and 19, total prostate volume (TPV) > 40 mL, and serum PSA > 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 33 publications
0
21
1
Order By: Relevance
“…However, some studies have reported negative results. For example, short-term lovastatin treatment does not seem to have any effect on IPSS, PV or PSA levels in men with prostatic enlargement due to presumed BPH and lipidemia [22]. Moreover, a large, double-blind, randomized, placebo-controlled clinical study found that atorvastatin had no effects on IPSS or PV over 6 months in 350 patients with presumed BPH who had serum LDLs in the range of 100-190 mg/dl [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have reported negative results. For example, short-term lovastatin treatment does not seem to have any effect on IPSS, PV or PSA levels in men with prostatic enlargement due to presumed BPH and lipidemia [22]. Moreover, a large, double-blind, randomized, placebo-controlled clinical study found that atorvastatin had no effects on IPSS or PV over 6 months in 350 patients with presumed BPH who had serum LDLs in the range of 100-190 mg/dl [23].…”
Section: Discussionmentioning
confidence: 99%
“…After four months of follow-up, men with lipidemia experience a statistically significant 0.98 ng/mL decrease in mean PSA from baseline. Men without lipidemia were also observed to have a decrease in PSA of 0.72 ng/mL, but this difference was not statistically significant (61). The investigators concluded that the latter result may have been observed due to the low power and duration of the study.…”
Section: Impact Of Statin Therapy On Psamentioning
confidence: 90%
“…Statin doses equal to and greater than 20 mg of simvastatin were associated with a greater than 8.5% greater decline in PSA levels and among men with a PSA level higher than 4.0 ng/mL, a decline of 12.5% was observed (60). Stamatiou et al (2008) investigated the effects of lovastatin on conventional medical treatment of lower urinary tract symptoms (61). Men older than 50 years of age with a total prostate volume greater than 40 mL and a serum PSA higher than 1.5 ng/mL were recruited.…”
Section: Impact Of Statin Therapy On Psamentioning
confidence: 94%
“…A recent community-based cohort study found a four-fold increased risk of BPH among diabetic men with LDL cholesterol in the highest tertile in comparison to men in the lowest tertile 55 . There has been very limited study of the effects of statins on BPH, with two studies showing no discernable effect 56, 57 and one study showing statin use to be associated with a 6.5-7-year delay in onset of moderate to severe LUTS or benign prostatic enlargement 58 . Several studies indicate that heart disease, diabetes and metabolic syndrome are associated with increased risk or severity of BPH 59-62 .…”
Section: Metabolism and The Prostatementioning
confidence: 99%